Analisis Kualitas Custumer Relationship Management dan Kepuasan Konsumen Sebagai Intervening Terhadap Loyalitas Keanggotaan Kopontren Fat-Hiyyah - Ading Rahman Sukmara; Aka Bonanza; Ferey Herman (STIKes Ibnu Sina Ajibarang, 2024)
The problems faced in this study include (1) How does the quality of customer relationship management affect the loyalty of Kopontren Fat-Hiyyah members? (2) How does consumer satisfaction affect the loyalty of Kopontren Fat-Hiyyah members? (3) How do the quality of customer relationship management and consumer satisfaction affect the loyalty of Kopontren Fat-Hiyyah members? This study aims to study, find out, and analyze (1) The effect of the quality of customer relationship management on the loyalty of Kopontren Fat-Hiyyah members. (2) The effect of consumer satisfaction on the loyalty of Kopontren Fat-Hiyyah members. (3) The effect of the quality of customer relationship management and consumer satisfaction on the loyalty of Kopontren Fat-Hiyyah members. The method used in this study is an explanatory survey, while the technical data analysis, namely validity test, reliability test, descriptive statistics, Inductive Statistical Analysis (Inferential) with Multiple Regression. The results of the study inform that (1) Customer relationship management has a positive and significant effect on membership loyalty. This means that if customer relationship management is improved, membership loyalty will also increase. (2) Member satisfaction has a positive and significant effect on membership loyalty. This means that if member satisfaction is increased, membership loyalty will also increase. (3) Customer relationship management and member satisfaction have a positive and significant effect on membership loyalty. This means that if customer relationship management and member satisfaction are increased, membership loyalty will also increase.